2017
DOI: 10.1111/cei.13057
|View full text |Cite
|
Sign up to set email alerts
|

H-ferritin and proinflammatory cytokines are increased in the bone marrow of patients affected by macrophage activation syndrome

Abstract: Macrophage activation syndrome (MAS) is hyperinflammatory life-threatening syndrome, associated typically with high levels of serum ferritin. This is an iron storage protein including heavy (H) and light (L) subunits, categorized on their molecular weight. The H-/L subunits ratio may be different in tissues, depending on the specific tissue and pathophysiological status. In this study, we analysed the bone marrow (BM) biopsies of adult MAS patients to assess the presence of: (i) H-ferritin and L-ferritin; (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 50 publications
(84 reference statements)
2
36
0
Order By: Relevance
“…Our results showed that FeH was more represented than FeL in BM biopsies of patients with AOSD and MAS, as previously reported in affected tissues 18,19,23,24 . Conversely, in sera of these patients, FeL was the predominant form, as reported by LC-MS/MS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that FeH was more represented than FeL in BM biopsies of patients with AOSD and MAS, as previously reported in affected tissues 18,19,23,24 . Conversely, in sera of these patients, FeL was the predominant form, as reported by LC-MS/MS.…”
Section: Discussionsupporting
confidence: 90%
“…Taking together these results and previous observations [51][52][53][54] , it could be possible to hypothesize that the stimulation with FeH could orientate the macrophages toward an M1 phenotype, suggesting the need of further studies to entirely clarify these issues. In addition, in inflammatory infiltrate of AOSD and MAS, a specific subset of macrophages was reported, displaying a specific CD68/H-ferritin phenotype expressing IL-12, which cannot be observed in normal tissues 19,23 . Finally, considering that the protein expressions did not confirmed the gene expressions observed following stimulation with ferritin on pro-inflammatory mediators, it could be possible to attribute the pro-inflammatory effects to FeH subunits of the ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, hyperferritinaemia plays an important role in the differentiation of MAS from other forms of HLH [36,39]. Furthermore, the expression of ferritin, in bone marrow of patients with AOSD and MAS, correlates with peripheral blood cytopenias and severity [40,41]. Moreover, AOSD and MAS have been included under the so-called 'hyperferritinemic syndrome' in which the pro-inflammatory proprieties of ferritin could be exacerbated in contributing to the inflammatory burden and development of a cytokine storm [18,41].…”
Section: Plos Onementioning
confidence: 99%
“…The exact role of the serum ferritin, and the mechanism triggering its release into circulation, during inflammatory conditions, are not known. Some controversy persists as to the role of ferritin in inflammation, with some authors defending that ferritin has an anti-inflammatory effect and others claiming that ferritin is pro-inflammatory [ 67 , 72 ].…”
Section: Different Pathogens Different Impacts On the Iron Metabomentioning
confidence: 99%